An Assessment of Glacier Inventories for the Third Pole Region - He, Xia; Zhou, Shiqiao (Frontiers in Earth Science, 2022)
Glacier inventory is the basic data for hydrological, water resources and climate change research. Glacier inventories have been created for the Third Pole Region (TPR) or high Asia, yet they are different in coverage area and vary largely in quality. It is thus necessary to assess their quality in order to provide information for potential users to choose the right glacier inventories. Using the analytic hierarchy process, this study selects eight assessment factors and assesses the comprehensive quality of eight glacier inventories of the TPR by grading. The assessment results indicate that the comprehensive quality of the small-scale glacier inventories of WHGI, KPGI, PGI-2 and SETPGI is generally higher than that of the large-scale ones of RGI, GGI18, CGI-2 and HKHGI. Of the latter, the quality-ranking order from high to low is CGI-2, GGI18, RGI and HKHGI. However, the comprehensive quality of CGI-2 and GGI18 is comparable over the CGI-2 area. The comprehensive quality of CGI-2, GGI18 and RGI exhibits clear spatial differentiation. Overall, it is higher for the inner TPR than for the surrounding areas. By merging products of the eight glacier inventories in terms of best-quality assessment units, a new glacier inventory product of best comprehensive quality was derived for the entire TPR. This new product largely resembles the spatial distribution of best-quality glacier inventories of the inventory-overlapping regions. Region-specifically, the CGI-2 and GGI18 are the best products for most part of the inside-China, except for partial area of the southeast Tibet, where the best is the SETPGI. The other main distributions of best products are the WHGI for the western Himalayas, the GGI18 and HKHGI for the Hindu Kush and the middle and eastern Himalayas, the PGI-2 for Pakistan, the KPGI for the Karakorum-Pamir area, and the GGI18 and CGI-2 for the Tianshan Mountains. The new product greatly promotes the quality of a single glacier inventory for the entire TPR. Finally, a database was created. It meets the needs of a variety of potential users including those who prefer to know a single quality or factor of a given glacier inventory of a region.